2014
DOI: 10.1080/07399332.2014.924939
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and the Utilization of Maternal Health Care Services in Nigeria

Abstract: Our aim in this study is to examine the association between women's lifetime experiences of physical, sexual, and emotional intimate partner violence (IPV) and the use of maternal health care services. We used data from the 2008 Nigeria Demographic and Health Survey. Analysis was based on responses from 17,476 women (for antenatal care [ANC]) and 17,412 (for delivery assisted by a skilled health provider) who had had deliveries in the 5 years preceding the survey. We found an overall IPV prevalence rate of 33.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
61
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 40 publications
9
61
0
Order By: Relevance
“…Our study showed that IPV is negatively associated with the use of ANC services such as registering for ANC check-up, taking iron and folic acid, dietary diversity, rest and sleep during the day and attending a mother's group meeting. These findings are supported by several studies performed in LMICs (33)(34)(35)(36). Our study findings are also similar to the study from India, which demonstrated that the utilisation of ANC components in pregnant women were negatively associated with physical violence during pregnancy (32).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our study showed that IPV is negatively associated with the use of ANC services such as registering for ANC check-up, taking iron and folic acid, dietary diversity, rest and sleep during the day and attending a mother's group meeting. These findings are supported by several studies performed in LMICs (33)(34)(35)(36). Our study findings are also similar to the study from India, which demonstrated that the utilisation of ANC components in pregnant women were negatively associated with physical violence during pregnancy (32).…”
Section: Discussionsupporting
confidence: 92%
“…For example, a nationally representative survey in India reported that women who experienced physical violence during pregnancy were less likely to receive prenatal care, home-visits from a health worker for a prenatal check-up, receive at least three prenatal care visits, and less likely to initiate prenatal care early in the pregnancy (32). Similar evidence has been reported from studies in Ghana, Bangladesh, Kenya and Nigeria (33)(34)(35)(36).…”
Section: Secondary Data Analysis Of National Surveys From 19 Differenmentioning
confidence: 64%
“…9 There is significant association between utilization of maternal health care services and IPV. 10 But some research found that there is no significant association between IPV and utilization of antenatal care services in Zambia. 11 Present study aimed to assess the impact of interpersonal violence on utilization of antenatal care by women of Tanzania.…”
Section: Introductionmentioning
confidence: 99%
“…Existing literature in South Asia and Africa suggests that presence of violence in a household may reduce the utilization of maternal and child health care services resulting in poor health status of both the mother and the child (Monemi, Pena, Ellsberg et al, 2003). Studies in Bangladesh and Nigeria found that intimate partner violence plays a significant role in lowering the utilization of reproductive health services among women and concluded that in addition to a wide range of socio-demographic factors, preventing physical and sexual violence needs to be considered as an important psychosocial determinant to increase utilization of reproductive health care services (Ononokpono and Azfredrick, 2014;Rahman, Nakamura, Seino et al, 2012). Using the Women's Reproductive Histories Survey (WRHS) in 2002 a study reveals that in India, among nuclear families, women with better marital relationships are more likely than their counterparts to use antenatal care services and deliver in a health-care facility (Allendorf, 2010).…”
Section: Introductionmentioning
confidence: 99%